English: A Discourse Study of The "Belajar Islam Pake Logika" Podcast - Muhammad Ikram Firda (Dialogia, 2025)
The lack of studies on logic-based da'wah strategies in digital conversation formats is an important gap in contemporary religious communication studies. This article aims to analyze how a rational approach is used in delivering Islamic messages through the YouTube podcast "Belajar Islam Pake Logika" with Felix Siauw and Raymond Chin. This study employs a qualitative approach in which descriptive procedures are used to organize the data, while Fairclough’s critical discourse study serves as the primary analytical framework. The object of study is the content of conversations in podcasts lasting more than one hour, with data in the form of complete transcripts obtained through documentation and non-intervention observation. The analysis was conducted through three stages: text analysis, discursive practices, and social practices. The findings show that logical argumentation, dialogic style, and social criticism are used as the main strategies of da'wah to build credibility and reach critical audiences. The findings indicate that rationality functions as a discursive resource that restructures how religious authority is articulated in digital media. This expands the theoretical understanding of da'wah communication by showing that meaning-making in contemporary Islamic discourse increasingly depends on dialogical reasoning rather than hierarchical textual claims. REFERENCES D’Ambrosio, Mariangela. “Emotions in Political Discourse and Social Narratives: Sociological Reflections on Traditional and New Media.” Society Register 6, no. 4 (2022): 101–16. https://doi.org/10.14746/sr.2022.6.4.06. Eka Arie Yuliyani, Hamsu Kadriyan, Mochammad Alfian Sulaksana, et al. “Edukasi Sadar Bising Sebagai Upaya Promotif Dan Preventif Terhadap Gangguan Dengar Melalui Media Podcast.” Jurnal Pengabdian Magister Pendidikan IPA 5, no. 2 (2022): 89–93. https://doi.org/10.29303/jpmpi.v5i2.1630. Elashrey, Mohamed Elsayed Ibrahim. “A Stylistic Approach to Power Relation Shifts in Arthur Miller’s The Crucible.” مجلة کلیة الآداب .جامعة بورسعید 21, no. 21 (2022): 22–40. https://doi.org/10.21608/jfpsu.2021.74436.1087. Fairclough, Norman. Critical Discourse Analysis. 0 ed. Routledge, 2013. https://doi.org/10.4324/9781315834368. Fattahizadeh, Fathyieh and Fereshteh Motamad Langrodi. “Application of Fairclough’s Critical Discourse Analysis Model to Quranic Verses Discussing Peaceful Dealing with Hypocrites.” Journal of Islamic Thought and Civilization 12, no. 1 (2022): 231–46. https://doi.org/10.32350/jitc.121.13. Fattahizadeh, Fathyieh and Fereshteh Motamad Langrodi. “Application of Fairclough’s Critical Discourse Analysis Model to Quranic Verses Discussing Peaceful Dealing with Hypocrites.” Journal of Islamic Thought and Civilization 12, no. 1 (2022): 231–46. https://doi.org/10.32350/jitc.121.13. Gee, James Paul, and Michael Handford. The Routledge Handbook of Discourse Analysis. 2nd ed. Routledge, 2023. https://doi.org/10.4324/9781003035244. Guihua, Luo, and Liu Mi. “The Concepts of Discourse and the Theoretical Genealogy of Discourse Analysis.” Social Science Research Frontiers, ahead of print, April 25, 2023. https://doi.org/10.57237/j.ssrf.2023.02.003. Harahap, Anjelin Rahmi Junaidi, Muhammad Fathurrahman Al-Anshori, and Kartini Kartini. “Metode Analisis Wacana Dalam Media Sosial.” Dakwatussifa: Journal of Da’wah and Communication 1, no. 2 (2022): 105–15. https://doi.org/10.56146/dakwatussifa.v1i2.54. Institute of Socio-Political Research of the Federal Center for Theoretical and Applied Sociology, Russian Academy of Sciences (ISPR FCTAS RAS), Nina A. Seliverstova, Julia A. Zubok, and Institute of Socio-Political Research of the Federal Center for Theoretical and Applied Sociology, Russian Academy of Sciences (ISPR FCTAS RAS). “Religious Identity in the Semantic Self-Regulation of Youth.” Research Result Sociology and Management 9, no. 2 (2023). https://doi.org/10.18413/2408-9338-2023-9-2-0-10. Khadiq. “Transformation of Islamic Religious Practices in the Digital Era: Opportunities and Challenges for Contemporary Da’wah.” Jurnal Dakwah 24, no. 2 (2023). https://doi.org/10.14421/jd.2023.24205. Li, Wengqian, and W. Shi. “English Advertising Slogans: A Modality System Analysis.” Asian Journal of Multilingualism and Applied Linguistics 1, no. 1 (2022): 25–29. https://doi.org/10.53402/ajmal.v1i1.61. Ligawan, Andry Saputra. “THE RELATIONSHIP BETWEEN RELIGION AND THE STATE: DISCOURSE ANALYSIS OF RELIGIOUS COMMUNICATION IN THE PUBLIC SPHERE.” Jurnal Bioconcetta 9, no. 2 (2024): 57–62. https://doi.org/10.22202/bc.2023.v9i2.7728. Lubis, Nikmah. “Intersection of Traditional Religious Authority and New Authority in the Digital Space of Indonesia.” FIKRAH 11, no. 1 (2023): 135. https://doi.org/10.21043/fikrah.v11i1.19678. Makhloufi, Imane Belkacem Mohammed. “A Critical Discourse Analysis of Modality in COVID-19 Speeches: A Systemic Functional Grammar Perspective.” Jordanian Educational Journal 10, no. 1 (2025): 331–53. https://doi.org/10.46515/jaes.v10i1.1332. Masasa, Karina. “The Role of Trust in the Discursive Construction of Legitimacy and Authority. The First Address on Covid-19 in Argentina.” Argumentation et Analyse Du Discours 28 (2022). https://doi.org/10.4000/aad.6480. Mattes, Mark. “Faith and Reason in the Reformations Ed. by Terence J. Kleven.” Lutheran Quarterly 36, no. 4 (2022): 454–56. https://doi.org/10.1353/lut.2022.0106. Mukhtidinov, Rashid. “Da’wah and Counter-Radicalism in Indonesia.” Dakwatuna: Jurnal Dakwah Dan Komunikasi Islam 9, no. 1 (2023): 67–78. https://doi.org/10.54471/dakwatuna.v9i1.2246. Nasution, Nadya Amalia and Alisya. “Islamic Leadership Narratives on YouTube: A Framing Analysis of Digital Da’wah Messages.” Ath-Thariq: Jurnal Dakwah Dan Komunikasi 8, no. 2 (2024): 116–27. https://doi.org/10.32332/ath-thariq.v8i2.8sw96g96. Nesterova, Natalia, and Anastasia Oreshkina. “The Paper Explores New Discursive Practices Determined by Media Convergence and New Communication Conditions. Based on the Case Study of the Program ‘We Speak Russian’ and the Podcast ‘What Is It in Russian?’ The Following Dynamic Changes Have Been Ident.” Philology & Human, no. 4 (December 2022): 26–42. https://doi.org/10.14258/filichel(2022)4-02. Nurul Khotimah and Fitri Shafa Kamila. “The Trends of Digital Da’wah: Cyber Media Analysis on Instagram Account.” Proceedings of the Saizu International Conference on Transdisciplinary Religious Studies, November 15, 2022, 1–11. https://doi.org/10.24090/icontrees.2022.217. Nurul Sulfiani, Munirah Munirah, and Haslinda Haslinda. “Analisis Tindak Tutur Ilokusi Dalam Podcast Deddy Corbuzier Dan Nadiem Makarim Pada Media Sosial Youtube.” DEIKTIS: Jurnal Pendidikan Bahasa Dan Sastra 2, no. 2 (2022): 114–28. https://doi.org/10.53769/deiktis.v2i2.251. Purwatiningsih, Sri Desti, and Sri Ekowati. “Interfaith Debate Through YouTube Media as an Effort to Educate and Fortify the Faith of the Ummah.” Technium Social Sciences Journal 30 (April 2022): 271–81. https://doi.org/10.47577/tssj.v30i1.6246. “Religion, Rationality and Justice – A Cause for Critical Reflection in the Contemporary Society.” Canadian Journal of Educational and Social Studies 2, no. 4 (2022). https://doi.org/10.53103/cjess.v2i4.51. Ross Arguedas, Amy A., Sumitra Badrinathan, Camila Mont’Alverne, Benjamin Toff, Richard Fletcher, and Rasmus Kleis Nielsen. “‘It’s a Battle You Are Never Going to Win’: Perspectives from Journalists in Four Countries on How Digital Media Platforms Undermine Trust in News.” Journalism Studies 23, no. 14 (2022): 1821–40. https://doi.org/10.1080/1461670X.2022.2112908. Sánchez-López, Elena. “Meaning, Degrees of Abstraction and Shared Knowledge.” In IVITRA Research in Linguistics and Literature, edited by Susana Rodríguez Rosique and Jordi M. Antolí Martínez, vol. 34. John Benjamins Publishing Company, 2023. https://doi.org/10.1075/ivitra.34.13san. Saragih, Ahmad Faza Fauzan, Rony Fernando Sagala, and Erwan Effendi. “Peran Media Sosial Dalam Membangun Dakwah Islam Yang Efektif.” Dakwatussifa: Journal of Da’wah and Communication 1, no. 2 (2022): 141–51. https://doi.org/10.56146/dakwatussifa.v1i2.59. Sharon, Tzlil. “Peeling the Pod: Towards a Research Agenda for Podcast Studies.” Annals of the International Communication Association 47, no. 3 (2023): 324–37. https://doi.org/10.1080/23808985.2023.2201593. Utomo, Deni Puji, and Rachmat Adiwijaya. “Representasi Moderasi Beragama Dalam Dakwah Habib Husein Ja’far Al-Hadar Pada Konten Podcast Noice ‘Berbeda Tapi Bersama.’” PUSAKA 10, no. 1 (2022): 212–23. https://doi.org/10.31969/pusaka.v10i1.675. Wu, Haibin. “Identity Construction through Lexical Choices: A Corpus-Based Approach.” Journal of Humanities, Arts and Social Science 7, no. 2 (2023): 401–7. https://doi.org/10.26855/jhass.2023.02.028. Zaid, Bouziane, Jana Fedtke, Don Donghee Shin, Abdelmalek El Kadoussi, and Mohammed Ibahrine. “Digital Islam and Muslim Millennials: How Social Media Influencers Reimagine Religious Authority and Islamic Practices.” Religions 13, no. 4 (2022): 335. https://doi.org/10.3390/rel13040335.